2010
DOI: 10.1111/j.1532-5415.2010.02819.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Medication Use in Nursing Home Residents with Advanced Dementia

Abstract: Objectives-Many medications commonly used to treat chronic conditions have unclear benefits for nursing home (NH) residents with advanced dementia. This study describes the pattern and factors associated with daily medication use in this population.Design, Setting, Participants-Residents with advanced dementia (N=323) from 22 Bostonarea NHs were followed prospectively for 18 months.Measurements-Data from residents' records were used to determine the number or daily medications, specific drugs prescribed, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
139
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(160 citation statements)
references
References 31 publications
(61 reference statements)
16
139
2
3
Order By: Relevance
“…These figures are higher than those reported in previous studies [2,[21][22][23], but do provide further evidence to support the conclusions of Tjia et al in their recent publication [2] that "most nursing home residents with advanced dementia receive medications of questionable benefit". Variations in the prevalence reported in these studies may be explained by the differences in medications included in and excluded from the analysis in each study; for example, in the study by Tjia et al [22], drugs prescribed on a when-required basis, topical preparations, vitamins (with the exception of vitamin D) and antimicrobials were not included whereas in the present study, regular and when-required medications, antimicrobials, topical and ophthalmic preparations and nutritional supplements were included.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…These figures are higher than those reported in previous studies [2,[21][22][23], but do provide further evidence to support the conclusions of Tjia et al in their recent publication [2] that "most nursing home residents with advanced dementia receive medications of questionable benefit". Variations in the prevalence reported in these studies may be explained by the differences in medications included in and excluded from the analysis in each study; for example, in the study by Tjia et al [22], drugs prescribed on a when-required basis, topical preparations, vitamins (with the exception of vitamin D) and antimicrobials were not included whereas in the present study, regular and when-required medications, antimicrobials, topical and ophthalmic preparations and nutritional supplements were included.…”
Section: Discussionsupporting
confidence: 57%
“…Other studies have reported lower numbers of medications per resident ranging from a median of 4 medications [23] to means of 5.9, 6.5 and 7.3 medications per person [21,22,25]. However, this may in part be explained by the differences in medications included in and excluded from the analysis in each study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Today, AD patients are broadly treated with antidementia drugs to improve cognitive and functional domains [13], and with neuroleptics, antidepressants, anxiolytics and other drugs to deal with behavioral and psychological symptoms [14]. So far, some studies have analyzed the drug prescription patterns in patients with AD, and most of them have focused on nursing homes, community-dwelling patients, or in specific drugs or families of drugs [15,16,17,18,19]. Besides, some authors describe medication patterns according to the severity of the dementia [20], but to our knowledge, there are no reports examining whether differences exist between the central nervous system (CNS) drug consumption pattern of individuals who are diagnosed as having AD, depending on the time elapsed between the first symptoms and the diagnosis.…”
Section: Introductionmentioning
confidence: 99%